The Making of an Avatar: Reading Sri Aurobindo Ghose (1872–1950). (1st August 2018) - Wolfers, Alex
Abstract : Sri Aurobindo Ghose (1872-1950), the revolutionary yogi of Pondicherry, was one of India's first global gurus of the modern age. Eluding easy classification, at different stages in his life he played the role of scholar, politician, poet, philosopher and mystic. Despite being the subject of considerable scholarship, Aurobindo has generally been presented as a disjointed figure, fragmented and constrained by disciplinary boundaries. Ongoing disputes within the wider Aurobindo community regarding his contested legacy have drawn attention to his (mis)appropriation by a resurgent Hindutva ethno-nationalism. Against the attempts by some to monumentalize Aurobindo as an infallible Avatar, this interdisciplinary review of the field of Aurobindo studies seeks to bring together a wide range of scholarly perspectives so as to serve as a meeting ground for multiple overlapping interpretations and future integral research. Indeed, only if we place Aurobindo's accession to Avatarhood in the context of his poetic, political and prophetic vision can we better understand how he reconciled the revolutionary and the mystic in his own life. Just as Aurobindo's theo-political reconfiguration of Hinduism under colonial conditions invokes an anticipatory horizon of individual and collective transformation, his conception of Avatarhood demands a mode of spiritual envisioning that sets the stage for utopian struggle.